Serum 25(OH) Vitamin D Concentrations in Horses: Effects of Age, Gender, Breed, Skin Colour and Season - Mohieddin Alemi; Saba Ahmadi Sheikhsarmast; Mehrdad Mohri (Veterinary Medicine and Science)
ABSTRACT Background The optimal amount of vitamin D required for the proper functioning of the immune system differs from the amount necessary for bone homeostasis. Furthermore, vitamin D metabolism varies among horses. Nevertheless, there is a dearth of information regarding reference values for vitamin D in horses, particularly in the Turkmen breed. The primary objectives of this study were to determine the concentrations of 25‐hydroxyvitamin D (25(OH)Vit D) in Turkmen, Thoroughbred and mixed Turkmen × Thoroughbred horses and to explore the effects of various factors on it and its relationship with serum biochemical variables and signalment data. Methods For the measurement of 25(OH)Vit D, 90 healthy horses (min age: 6 months; max age: 10 years) that were stable in the north of Iran (37°17′ N, 55°18′ E) were selected for clinical examination and complete blood biochemistry analysis. The horses were categorised into different groups based on sex, season (spring, n = 45; autumn, n = 45), breed (Turkmen, Thoroughbred and mixed Turkmen × Thoroughbred), age (< 2 years, 2–8 years and > 8 years) and skin colour. Sampling was performed only once from each horse. Results In this study, the median serum concentration of 25(OH)Vit D in the sampled horses was 17.42 ng/mL (IQR: 9.82–30.85). The serum 25(OH)Vit D concentration was significantly lower in autumn (median: 15.83 ng/mL and IQR: 8.67–54.68) than in spring (median: 18.02 ng/mL and IQR: 13.77–27.54) and was also lower in Turkmen horses (median: 15.83 ng/mL and IQR: 11.63–23.12) than in mixed breed horses (median: 17.72 ng/mL and IQR: 8.94–51.67) (p ≤ 0.05). Conclusion According to the results of the present study, the season had a significant effect on the serum 25(OH)Vit D concentration, and this difference was also observed between Turkmen horses and mixed‐bred horses (p ≤ 0.05). It is unclear whether the time of sun exposure or vitamin D content of diet causes the seasonal difference of 25(OH)Vit D concentration.